O Município de Armação dos Búzios e a Educação: a escola pública municipal na aldeia de pescadores que se tornou município e pólo internacional de turismo - Paiva, Ana Maria Severiano de (2004)
This thesis presents the outcomes of a research whose goal was to study the achievements of the federal education policies at the town of Armação dos Búzios between 1997 and 2003. On the hypothesis that there lacks homogeneousness in the policies which aim at guaranteeing the right to education, the analysis of the public education policies of a town shall take into consideration not only the federal overall direction, but also the history of the place and its people. The collected data regarding Armação dos Búzios pointed out still another relevant aspect: two are the mainentities which bear influence over the creation of such policies, namely the federal body and the school itself. Since its existence as an emancipated (1995) town (whereupon its first municipal government was set, in 1997), Armação dos Búzios had been witnessing an increase in the offer of education, until that town has finally been able to cope with the whole Basic Education, in 2003. The public school has mostly been the source of local education leaders at that place. It is the history of the place and its people that enables a better understanding of the federal public policies as practiced in Armação dos Búzios.